Clinical and Biochemical Evaluation of Subacute (De Ouervain’s) Thyroiditis - Fariduddin, M; Sultana, Nusrat; Badiuzzaman, M; Abdullah, ABM; Hasanat, M Abul (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Subacute thyroiditis is an important cause of thyrotoxicosis, often misdiagnosed as Graves’ disease and given anti-thyroid drugs. Etiological diagnosis can yield proper guideline of management and a good result. Objectives: To see the clinical, biochemical and isotope profile of subacute thyroiditis. Methods: A total of 45 cases [36 females, 9 males; age (mean ± SD): 33± 4.7 yr] were recruited from Endocrine outpatient department of Bangabandhu Sheikh Mujib Medical University (BSMMU) to see thyroid hormones and isotope scan. Results: Most of the patients had a history of sore throat (84.4%). All had painful thyroid gland with or without dysphagia, palpitation (93%), fever (91%), sweating and heat intolerance (80%) and IBS like symptoms was 46%. Among 36 females, 16 patients (44.4%) presented with oligomenorrhea/amenorrhea. Clinically palpable thyromegaly was present in 33 cases (73%), which was diffuse in 24 patients (73%), resting tachycardia in 35(78%) while anaemia in 23(51%). A few cases (13/45) had raised blood pressure. Elevation of thyroid hormone was found in 44(97.7%), but in most cases it was mild; little reduction of TSH (0.1-0.3mIU) was present in 43 (95%). Characteristically, low radio-iodine uptake (< 5%) in 2 hours and 24 hours was found in 100% and thyroid scan revealed uniform uptake in all cases. ESR was raised in 100% cases and leucocytosis was present in 9(20%). Conclusion: It is concluded that subacute thyroiditis can be diagnosed on careful clinical examination. As it is a self limiting disease and does not usually need any anti-thyroid medication, subacute thyroiditis should be excluded in thyrotoxic patients before initiating anti-thyroid drugs. Key words: Subacute thyroiditis; clinical and biochemical profile DOI: 10.3329/bsmmuj.v3i2.7057 BSMMU J 2010; 3(2): 82-85